Konstruksi Hukum Terhadap Kewajiban Koordinasi PPNS Kepada Kepolisian Dalam Menyidik Pencucian Uang - Nurlaily, Hasrina (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2023)
Civil Servant Investigators (CSI) can investigate money laundering (ML) crimes. The process of investigating money laundering by CSI is contained in Law 8/2010 and in the Indonesian Constitutional Court No. 15/PUU-XIX/2021 Decision. Given that CSI is governed by and works in tandem with the Indonesian National Police, these laws still call for greater regulation for CSI to fulfill and apply the multidoor system concept and the rapid, simple, and low-cost principle as crime investigators for ML. This study aims to clarify why it is critical to implement legal construction in connection with the ML investigation by CSI under the relevant concepts and principles to maximize the handling of ML in the future. This paper used normative juridical, statutory, and conceptual approaches. The findings of this study are expected to serve as a guide for the CSI in investigating ML during transferring the findings of investigations to the Public Prosecutor, leveling perceptions among law enforcement officials, and providing support for investigators balanced with coordination and cooperation among officials so that effective and efficient law enforcement can be achieved.